Post-small incision lenticule extraction phacoemulsification with multifocal IOL implantation: A case report - Sri Ganesh; Sheetal Brar; Karthik Sriprakash (Indian Journal of Ophthalmology, 2019)
A 54-year-old patient presented with cataract, 5 years after undergoing SMILE for high myopia in both eyes. He was motivated in achieving spectacle free vision and his post SMILE-induced aberrations were minimal, due to which he was found suitable for a trifocal IOL implant. Of the various methods considered, the IOL power predicted by a novel combined telecentric keratometry and swept source OCT-based method was finally selected. One month post-operatively, the patient achieved a binocular UDVA of 20/20p and near vision of N.6, suggesting that newer IOL formulae could be superior in providing satisfactory outcomes in post refractive patients.